Morphological change of shorelines in the presence of groins and offshore breakwaters - Nakatani, Tsuyoshi; Suphat Vongvisessomjai; Abe, Tetsuo; Prida Thimakorn; The Royal Thai Government (Bangkok : Asian Institute of Technology, 1982)
In order to obtain basic aspect on beach deformation in the presence of both normal and inclined groins and offshore breakwaters, the hydraulic model experiments have been conducted for oblique incoming waves. The model beach with slope 1/15 was made of fine sand and waves of two kinds of steepness were used representing an ordinary beach and a storm beach respectively. Furthermore, Tombola. developments have been observed by changing the ratios of the breakwater length to distance offshore. Throughout these experiments it has been verified that the longshore transport is no longer considered to be the only predominant factor but the onshore-offshore transport is equally effective on beach deformation in case of a storm beach. It has been also clarified that the location of off shore breakwaters is an important factor on tombol a developments. An analytical solution for beach development with groin based upon the one line theory is presented. Effects of wave diffraction, wave refraction, and wave reflection are neglected. However the second order influence of the incident wave angle on alongshore transport rate and the length of groin are taken into consideration and are found to be important on beach deformation. Applications of the obtained solution to experimental results at the up-coast of groins are finally confirmed.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1982
Keywords: Coast changes; Breakwaters